Temperature change resistant glass material and preparation method thereof
By spraying modified polyurea and functionalized alumina coating materials on the glass surface, the problem of existing glass materials being prone to dirt during long-term use is solved, and the effects of anti-fouling, self-repair and heat conduction are achieved, and the overall performance of the glass is improved.
Patent Information
- Application Number
- CN202411904732.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-12-23
AI Technical Summary
Existing glass materials are prone to dirt after long-term sun exposure and wind and rain, affecting the visual effect, and lack effective anti-fouling ability.
The coating material is prepared by mixing the modified polyurea with functionalized alumina, and spraying it on the glass surface and drying it to form a temperature-resistant glass material. The material uses a combination of modified polyurea and functionalized alumina to form a dense protective film that prevents the penetration of water, oil and stains.
The anti-fouling effect on the glass surface is achieved, visual cleanliness is improved, and the durability and impact resistance of the glass are enhanced by the self-healing ability of modified polyurea and the thermal conductivity of alumina.
Abstract
Description
Technical Field
[0001] The invention relates to the field of glass, in particular to a temperature-change resistant glass material and a preparation method thereof. Background Art
[0002] Since its appearance, glass has experienced thousands of years of development, from ancient Chinese colored glaze, to Roman mosaic, to the glass manufacturing industry during the Industrial Revolution. With the advancement of science and technology, the application areas of glass have gradually expanded, covering daily utensils, architectural decoration, glass fiber, electronic information and biomaterials and other aspects. Among them, in the field of architectural decoration alone, it can be divided into flat glass, decorative glass, safety glass and energy-saving glass according to different functions.
[0003] With the development of social economy and the continuous improvement of people's living standards, the requirements for the safety performance of glass in buildings are getting higher and higher. Safety glass refers to glass that can withstand severe vibration or impact without breaking, or glass that is not easy to hurt people even if it breaks. It is widely used in cars, airplanes, and building doors and windows, etc. However, with long-term exposure to sunlight, wind and rain, dirt will be produced on the glass, thus affecting the visual effect. Therefore, this article introduces a temperature-resistant glass material with anti-fouling ability. Summary of the invention
[0004] The object of the present invention is to provide a temperature-change resistant glass material and a preparation method thereof, so as to solve the problems existing in the prior art.
[0005] A temperature-change resistant glass material, wherein the temperature-change resistant glass material is prepared by mixing modified polyurea with functionalized alumina to prepare a coating material, spraying the coating material on a glass surface, and drying the coating material;
[0006] The functionalized alumina is prepared by reacting alumina with 3-aminopropyltrimethoxysilane, 4-bromo-2-hydroxybenzaldehyde and 4-aminopyridine in sequence;
[0007] The glass is prepared by immersing whisker silicon in aluminum hydroxide solution, heating with nano silicon dioxide, lithium oxide, sodium carbonate and titanium dioxide, mixing and annealing.
[0008] The modified polyurea is prepared by reacting polyaspartic acid ester resin F420, polyaspartic acid ester resin F524, hexamethylene diisocyanate-based polyisocyanate trimer, functionalized monomer and end-capping agent;
[0009] The functionalized monomer is prepared by reacting 2,2'-bis(trifluoromethyl)diaminobiphenyl and diethyl maleate;
[0010] The end-capping agent is prepared by reacting 4',4" (5")-diaminodibenzo-15-crown ether-5 and diethyl maleate.
[0011] A method for preparing a temperature-resistant glass material, the method for preparing the temperature-resistant glass material mainly comprising the following preparation steps:
[0012] (1) 20 to 30 parts of silicon whiskers, 40 to 50 parts of nano silicon dioxide, 2 to 4 parts of lithium oxide, 2 to 3 parts of sodium carbonate, and 4 to 5 parts of titanium dioxide are taken by weight, and the silicon whiskers are immersed in an aluminum hydroxide solution for 2 to 3 minutes, taken out, and nano silicon dioxide, lithium oxide, sodium carbonate, and titanium dioxide are added, and the solution is kept at 1600 to 1700° C. for 2 to 4 hours to obtain glass liquid, and the glass liquid is poured onto a graphite heating plate to obtain a plate, and the plate is transferred to an annealing furnace at 500 to 600° C. for annealing for 100 to 140 minutes, and naturally cooled to room temperature to obtain glass;
[0013] (2) Alumina, ethanol solution and 3-aminopropyltrimethoxysilane are mixed in a mass ratio of 1:80-100:0.3-0.5, ultrasonicated for 25-35 minutes, stirred at 50-70°C and 200-300 r / min for 22-26 hours, filtered, washed with ethanol for 3-5 times, and dried to obtain pre-modified alumina; the pre-modified alumina and acetonitrile are mixed in a mass ratio of 1:10-12, 3-aminopropyltrimethoxysilane is added in an equal molar ratio, and the mixture is stirred for 2 hours. Amount of 4-bromo-2-hydroxybenzaldehyde is added, stirred at 200-300 r / min for 14-18 hours, filtered, washed with ethanol for 3-5 times, and dried to obtain modified alumina; modified alumina, 4-aminopyridine and acetone are mixed in a mass ratio of 1:0.1-0.2:8-10, stirred at 50-60°C and 200-300 r / min for 11-13 hours, filtered, washed with acetone for 3-5 times, and dried to obtain functionalized alumina;
[0014] (3) Mix 2,2'-bis(trifluoromethyl)diaminobiphenyl and methanol in a mass ratio of 1:5-7.
[0015] 200~300r / min, under nitrogen protection, stir for 10~20min, heat to 50~55℃, add diethyl maleate (2 times the molar amount of 2,2'-bis(trifluoromethyl)diaminobiphenyl) at a uniform speed within 8~10min, heat to
[0016] 75-85°C, continue stirring for 34-36 hours, and dry at 50-60°C for 22-24 hours to obtain a functionalized monomer;
[0017] (4) 4',4" (5")-diaminodibenzo-15-crown-5 and methanol are mixed in a mass ratio of 1:5-7, stirred at 200-300 r / min under nitrogen protection for 10-20 min, heated to 50-55° C., and an equal molar amount of diethyl maleate is added to 4',4" (5")-diaminodibenzo-15-crown-5 at a uniform rate within 8-10 min, heated to 75-85° C., stirred for 34-36 h, and dried at 50-60° C. for 22-24 h to obtain a capping agent;
[0018] (5) Mix polyaspartic acid resin F420, polyaspartic acid resin F524, hexamethylene diisocyanate-based polyisocyanate trimer and tetrahydrofuran in a molar ratio of 1:1:1.8-2:8-10, stir at 50-70°C and 200-300 r / min for 50-70 min, cool to 40-60°C, continue stirring, uniformly add a mixed solution of 3-4 times the molar amount of polyaspartic acid resin F420 within 8-10 min, cool to 30-50°C, continue stirring for 2-4 h, and obtain a modified polyurea;
[0019] (6) The modified polyurea and the functionalized alumina are mixed in a mass ratio of 1:0.15-0.25, stirred at 30-50°C and 200-300 r / min for 4-6 min to obtain a coating material, sprayed on the glass surface, vacuum dried at 50-70°C for 70-74 h, and allowed to stand at room temperature for 70-74 h to obtain a temperature-resistant glass.
[0020] As an optimization, the length of the silicon whisker in step (1) is 1 to 5 μm.
[0021] As an optimization, the aluminum hydroxide solution in step (1) is prepared by uniformly mixing aluminum hydroxide and water in a mass ratio of 1:3 to 5.
[0022] As an optimization, the thickness of the plate in step (1) is 18 to 22 mm.
[0023] As an optimization, the ethanol solution in step (2) is prepared by uniformly mixing ethanol and water in a mass ratio of 1:1.
[0024] As an optimization, the specific operation of the drying in step (2) is vacuum drying at -10 to 0°C for 22 to 26 hours.
[0025] As an optimization, the mixed solution in step (5) is prepared by uniformly mixing the functionalized monomer, the end-capping agent and tetrahydrofuran in a molar ratio of 3-5:1:8-10.
[0026] As an optimization, the spraying thickness of the coating material in step (6) is 2 mm.
[0027] Compared with the prior art, the beneficial effects achieved by the present invention are:
[0028] When preparing the temperature-change resistant glass material, the present invention soaks whisker silicon in an aluminum hydroxide solution, and then heats, mixes, and anneals with nano silicon dioxide, lithium oxide, sodium carbonate, and titanium dioxide to obtain glass; reacts aluminum oxide with 3-aminopropyltrimethoxysilane, 4-bromo-2-hydroxybenzaldehyde, and 4-aminopyridine in sequence to obtain functionalized aluminum oxide; reacts 2,2'-bis(trifluoromethyl)diaminobiphenyl with diethyl maleate to obtain a functionalized monomer; The end-capping agent is prepared by reacting 4',4" (5")-diaminodibenzo-15-crown ether-5 with diethyl maleate; the modified polyurea is prepared by reacting polyaspartic acid ester resin F420, polyaspartic acid ester resin F524, hexamethylene diisocyanate-based polyisocyanate trimer, functionalized monomer and the end-capping agent; the modified polyurea is mixed with functionalized alumina to prepare a coating material, which is sprayed on a glass surface and dried to prepare a temperature-resistant glass material.
[0029] First, the whisker silicon is immersed in an aluminum hydroxide solution, and then heated, mixed, and annealed with nano-silicon dioxide, lithium oxide, sodium carbonate, and titanium dioxide to obtain glass; the aluminum oxide is reacted with 3-aminopropyltrimethoxysilane, 4-bromo-2-hydroxybenzaldehyde, and 4-aminopyridine in sequence to obtain functionalized aluminum oxide; aluminum hydroxide is loaded on the surface of the whisker silicon, and high temperature causes the aluminum hydroxide to be converted into aluminum oxide, which can reduce the thermal expansion coefficient of the glass, thereby achieving the effect of temperature resistance; aluminum oxide, as an inorganic non-metallic material, can enhance the thermal conductivity of the material, react with 3-aminopropyltrimethoxysilane to make its surface rich in amino groups, and then react with 4-bromo-2-hydroxybenzaldehyde to partially form conjugated rings, thereby making the coating resistant to aging; and then react with 4-aminopyridine to form a ligand that achieves a host-guest effect with the crown ether, thereby achieving a better combination effect with polyurea and making the coating have self-repairing ability.
[0030] Secondly, 2,2'-bis(trifluoromethyl)diaminobiphenyl and diethyl maleate are reacted to obtain a functionalized monomer; 4',4" (5")-diaminodibenzo-15-crown ether-5 and diethyl maleate are reacted to obtain a capping agent; polyaspartic acid resin F420, polyaspartic acid resin F524, hexamethylene diisocyanate-based polyisocyanate trimer, functionalized monomer and capping agent are reacted to obtain a modified polyurea; the modified polyurea is mixed with functionalized alumina to obtain a coating material, which is sprayed on the glass surface and dried to obtain a heat-resistant The fluorine atom has a very strong electronegativity, which makes the bond energy of the carbon-fluorine bond larger and the surface tension extremely low, so that the modified polyurea can form a dense protective film on the surface of the material, thereby preventing the penetration of water, oil and stains, and achieving an anti-fouling effect; due to the presence of crown ether on the prepared modified polyurea, it can achieve a better bonding effect with the functionalized alumina, and make the coating have the ability of self-repair. The polyurea coating often shows a high failure strain when subjected to impact load, thereby absorbing or dissipating the huge energy generated by the impact load, so that the material has impact resistance. DETAILED DESCRIPTION
[0031] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0032] Embodiment 1:
[0033] A method for preparing a temperature-resistant glass material mainly comprises the following preparation steps:
[0034] (1) 25 parts of silicon whiskers, 40 parts of nano silicon dioxide, 2 parts of lithium oxide, 2 parts of sodium carbonate, and 4 parts of titanium dioxide are taken by weight, and the silicon whiskers are immersed in an aluminum hydroxide solution for 2 minutes, taken out, and nano silicon dioxide, lithium oxide, sodium carbonate, and titanium dioxide are added, and the solution is kept at 1600° C. for 2 hours to obtain glass liquid, and the glass liquid is poured onto a graphite heating plate to obtain a plate, which is transferred to an annealing furnace at 500° C. for annealing for 100 minutes, and naturally cooled to room temperature to obtain glass;
[0035] (2) Alumina, ethanol solution and 3-aminopropyltrimethoxysilane were mixed in a mass ratio of 1:80:0.3, ultrasonicated for 25 minutes, stirred at 50°C and 200 r / min for 22 hours, filtered, washed with ethanol three times, and dried to obtain pre-modified alumina; pre-modified alumina and acetonitrile were mixed in a mass ratio of 1:10, 4-bromo-2-hydroxybenzaldehyde in an equal molar amount of 3-aminopropyltrimethoxysilane was added, stirred at 200 r / min for 14 hours, filtered, washed with ethanol three times, and dried to obtain modified alumina; modified alumina, 4-aminopyridine and acetone were mixed in a mass ratio of 1:0.1:8, stirred at 50°C and 200 r / min for 11 hours, filtered, washed with acetone three times, and dried to obtain functionalized alumina;
[0036] (3) 2,2'-bis(trifluoromethyl)diaminobiphenyl and methanol were mixed in a mass ratio of 1:5, stirred at 200 r / min under nitrogen protection for 10 min, heated to 50°C, and diethyl maleate in an amount twice the molar amount of 2,2'-bis(trifluoromethyl)diaminobiphenyl was uniformly added within 8 min, heated to 75°C, stirred for 34 h, and dried at 50°C for 22 h to obtain a functionalized monomer;
[0037] (4) 4',4" (5")-diaminodibenzo-15-crown ether-5 and methanol were mixed in a mass ratio of 1:5, stirred at 200 r / min under nitrogen protection for 10 min, heated to 50°C, and added with an equal molar amount of diethyl maleate to 4',4" (5")-diaminodibenzo-15-crown ether-5 at a uniform rate over 8 min, heated to 75°C, stirred for 34 h, and dried at 50°C for 22 h to obtain a capping agent;
[0038] (5) Mix polyaspartic acid resin F420, polyaspartic acid resin F524, hexamethylene diisocyanate-based polyisocyanate trimer and tetrahydrofuran in a molar ratio of 1:1:1.8:8, stir at 50°C, 200 r / min for 50 min, cool to 40°C, continue stirring, uniformly add a mixed solution of 3 times the molar amount of polyaspartic acid resin F420 within 8 min, cool to 30°C, continue stirring for 2 h, and obtain a modified polyurea;
[0039] (6) The modified polyurea and the functionalized alumina were mixed in a mass ratio of 1:0.15, stirred at 30°C and 200 r / min for 4 min to obtain a coating material, sprayed on the glass surface, vacuum dried at 50°C for 70 h, and allowed to stand at room temperature for 70 h to obtain a temperature-resistant glass.
[0040] The length of the silicon whisker in step (1) is 1 μm.
[0041] The aluminum hydroxide solution in step (1) is prepared by uniformly mixing aluminum hydroxide and water in a mass ratio of 1:3.
[0042] The thickness of the plate in step (1) is 18 mm.
[0043] The ethanol solution in step (2) is prepared by uniformly mixing ethanol and water in a mass ratio of 1:1.
[0044] The specific operation of the drying in step (2) is vacuum drying at -10°C for 22 hours.
[0045] The mixed solution in step (5) is prepared by uniformly mixing the functionalized monomer, the end-capping agent and tetrahydrofuran in a molar ratio of 3:1:8.
[0046] The spraying thickness of the coating material in step (6) is 2 mm.
[0047] Embodiment 2:
[0048] A method for preparing a temperature-resistant glass material mainly comprises the following preparation steps:
[0049] (1) 25 parts of silicon whiskers, 45 parts of nano silicon dioxide, 3 parts of lithium oxide, 2.5 parts of sodium carbonate, and 4.5 parts of titanium dioxide are taken by weight, and the silicon whiskers are immersed in an aluminum hydroxide solution for 2.5 minutes, taken out, and nano silicon dioxide, lithium oxide, sodium carbonate, and titanium dioxide are added, and the solution is kept at 1650° C. for 3 hours to obtain glass liquid, and the glass liquid is poured onto a graphite heating plate to obtain a plate, which is then transferred to an annealing furnace at 550° C. for annealing for 120 minutes, and naturally cooled to room temperature to obtain glass;
[0050] (2) Alumina, ethanol solution and 3-aminopropyltrimethoxysilane were mixed in a mass ratio of 1:90:0.4, ultrasonicated for 30 minutes, stirred at 60°C and 250 r / min for 24 hours, filtered, washed with ethanol for 4 times, and dried to obtain pre-modified alumina; pre-modified alumina and acetonitrile were mixed in a mass ratio of 1:11, 4-bromo-2-hydroxybenzaldehyde in an equal molar amount of 3-aminopropyltrimethoxysilane was added, stirred at 250 r / min for 16 hours, filtered, washed with ethanol for 4 times, and dried to obtain modified alumina; modified alumina, 4-aminopyridine and acetone were mixed in a mass ratio of 1:0.15:9, stirred at 55°C and 250 r / min for 12 hours, filtered, washed with acetone for 4 times, and dried to obtain functionalized alumina;
[0051] (3) Mix 2,2'-bis(trifluoromethyl)diaminobiphenyl and methanol in a mass ratio of 1:6.
[0052] 250r / min, under nitrogen protection, stir for 15min, heat to 52.5℃, add diethyl maleate at a rate of 2 times the molar amount of 2,2'-bis(trifluoromethyl)diaminobiphenyl at a uniform rate within 9min, heat to 80℃, continue stirring for 35h, dry at 55℃ for 23h to obtain a functionalized monomer;
[0053] (4) 4',4" (5")-diaminodibenzo-15-crown ether-5 and methanol were mixed in a mass ratio of 1:6, stirred at 250 r / min under nitrogen protection for 15 min, heated to 52.5°C, and added with an equal molar amount of diethyl maleate to 4',4" (5")-diaminodibenzo-15-crown ether-5 at a uniform rate over 9 min, heated to 80°C, stirred for 35 h, and dried at 55°C for 23 h to obtain a capping agent;
[0054] (5) Mix polyaspartic acid resin F420, polyaspartic acid resin F524, hexamethylene diisocyanate-based polyisocyanate trimer and tetrahydrofuran in a molar ratio of 1:1:1.9:9, stir at 60°C and 250 r / min for 60 min, cool to 50°C, continue stirring, uniformly add 3.5 times the molar amount of polyaspartic acid resin F420 in 9 min, cool to 40°C, continue stirring for 3 h, and obtain modified polyurea;
[0055] (6) The modified polyurea and the functionalized alumina were mixed in a mass ratio of 1:0.2, stirred at 40°C and 250 r / min for 5 min to obtain a coating material, sprayed on the glass surface, vacuum dried at 60°C for 72 h, and allowed to stand at room temperature for 72 h to obtain a temperature-resistant glass.
[0056] The length of the silicon whisker in step (1) is 3 μm.
[0057] The aluminum hydroxide solution in step (1) is prepared by uniformly mixing aluminum hydroxide and water in a mass ratio of 1:4.
[0058] The thickness of the plate in step (1) is 20 mm.
[0059] The ethanol solution in step (2) is prepared by uniformly mixing ethanol and water in a mass ratio of 1:1.
[0060] The specific operation of the drying in step (2) is vacuum drying at -5°C for 24 hours.
[0061] The mixed solution in step (5) is prepared by uniformly mixing the functionalized monomer, the end-capping agent and tetrahydrofuran in a molar ratio of 4:1:9.
[0062] The spraying thickness of the coating material in step (6) is 2 mm.
[0063] Embodiment 3:
[0064] A method for preparing a temperature-resistant glass material mainly comprises the following preparation steps:
[0065] (1) 30 parts of silicon whiskers, 50 parts of nano silicon dioxide, 4 parts of lithium oxide, 3 parts of sodium carbonate, and 5 parts of titanium dioxide are taken by weight, and the silicon whiskers are immersed in an aluminum hydroxide solution for 3 minutes, taken out, and nano silicon dioxide, lithium oxide, sodium carbonate, and titanium dioxide are added, and the solution is kept at 1700° C. for 4 hours to obtain glass liquid, and the glass liquid is poured onto a graphite heating plate to obtain a plate, which is transferred to an annealing furnace at 600° C. for annealing for 140 minutes, and naturally cooled to room temperature to obtain glass;
[0066] (2) Alumina, ethanol solution and 3-aminopropyltrimethoxysilane were mixed in a mass ratio of 1:100:0.5, ultrasonicated for 35 minutes, stirred at 70°C and 300 r / min for 26 hours, filtered, washed with ethanol 5 times, and dried to obtain pre-modified alumina; pre-modified alumina and acetonitrile were mixed in a mass ratio of 1:12, 4-bromo-2-hydroxybenzaldehyde in an equal molar amount of 3-aminopropyltrimethoxysilane was added, stirred at 300 r / min for 18 hours, filtered, washed with ethanol 5 times, and dried to obtain modified alumina; modified alumina, 4-aminopyridine and acetone were mixed in a mass ratio of 1:0.2:10, stirred at 60°C and 300 r / min for 13 hours, filtered, washed with acetone 5 times, and dried to obtain functionalized alumina;
[0067] (3) 2,2'-bis(trifluoromethyl)diaminobiphenyl and methanol were mixed in a mass ratio of 1:7, stirred at 300 r / min under nitrogen protection for 20 min, heated to 55°C, and diethyl maleate in an amount twice the molar amount of 2,2'-bis(trifluoromethyl)diaminobiphenyl was uniformly added within 10 min, heated to 85°C, stirred for 36 h, and dried at 60°C for 24 h to obtain a functionalized monomer;
[0068] (4) 4',4" (5")-diaminodibenzo-15-crown ether-5 and methanol were mixed in a mass ratio of 1:7, stirred at 300 r / min under nitrogen protection for 20 min, heated to 55°C, and added with an equal molar amount of diethyl maleate to 4',4" (5")-diaminodibenzo-15-crown ether-5 at a uniform rate within 10 min, heated to 85°C, stirred for 36 h, and dried at 60°C for 24 h to obtain a capping agent;
[0069] (5) Mix polyaspartic acid resin F420, polyaspartic acid resin F524, hexamethylene diisocyanate-based polyisocyanate trimer and tetrahydrofuran in a molar ratio of 1:1:2:10, stir at 70°C and 300 r / min for 70 min, cool to 60°C, continue stirring, uniformly add a mixed solution of 4 times the molar amount of polyaspartic acid resin F420 within 10 min, cool to 50°C, continue stirring for 4 h, and obtain a modified polyurea;
[0070] (6) The modified polyurea and the functionalized alumina were mixed in a mass ratio of 1:0.25, stirred at 50°C and 300 r / min for 6 min to obtain a coating material, sprayed on the glass surface, vacuum dried at 70°C for 74 h, and allowed to stand at room temperature for 74 h to obtain a temperature-resistant glass.
[0071] The length of the silicon whisker in step (1) is 5 μm.
[0072] The aluminum hydroxide solution in step (1) is prepared by uniformly mixing aluminum hydroxide and water in a mass ratio of 1:5.
[0073] The thickness of the plate in step (1) is 22 mm.
[0074] The ethanol solution in step (2) is prepared by uniformly mixing ethanol and water in a mass ratio of 1:1.
[0075] The specific operation of the drying in step (2) is vacuum drying at 0°C for 26 hours.
[0076] The mixed solution in step (5) is prepared by uniformly mixing the functionalized monomer, the end-capping agent and tetrahydrofuran in a molar ratio of 5:1:10.
[0077] The spraying thickness of the coating material in step (6) is 2 mm.
[0078] Comparative Example 1:
[0079] A method for preparing a temperature-resistant glass material mainly comprises the following preparation steps:
[0080] (1) 25 parts of whisker silicon, 45 parts of nano-silicon dioxide, 3 parts of lithium oxide, 2.5 parts of sodium carbonate, and 4.5 parts of titanium dioxide are mixed by weight, and the mixture is kept at 1650° C. for 3 hours to obtain glass liquid, and the glass liquid is poured onto a graphite heating plate to obtain a plate, which is then transferred to an annealing furnace at 550° C. for annealing for 120 minutes and naturally cooled to room temperature to obtain glass;
[0081] (2) Alumina, ethanol solution and 3-aminopropyltrimethoxysilane were mixed in a mass ratio of 1:90:0.4, ultrasonicated for 30 minutes, stirred at 60°C and 250 r / min for 24 hours, filtered, washed with ethanol for 4 times, and dried to obtain pre-modified alumina; pre-modified alumina and acetonitrile were mixed in a mass ratio of 1:11, 4-bromo-2-hydroxybenzaldehyde in an equal molar amount of 3-aminopropyltrimethoxysilane was added, stirred at 250 r / min for 16 hours, filtered, washed with ethanol for 4 times, and dried to obtain modified alumina; modified alumina, 4-aminopyridine and acetone were mixed in a mass ratio of 1:0.15:9, stirred at 55°C and 250 r / min for 12 hours, filtered, washed with acetone for 4 times, and dried to obtain functionalized alumina;
[0082] (3) Mix 2,2'-bis(trifluoromethyl)diaminobiphenyl and methanol in a mass ratio of 1:6.
[0083] 250r / min, under nitrogen protection, stir for 15min, heat to 52.5℃, add diethyl maleate at a rate of 2 times the molar amount of 2,2'-bis(trifluoromethyl)diaminobiphenyl at a uniform rate within 9min, heat to 80℃, continue stirring for 35h, dry at 55℃ for 23h to obtain a functionalized monomer;
[0084] (4) 4',4" (5")-diaminodibenzo-15-crown ether-5 and methanol were mixed in a mass ratio of 1:6, stirred at 250 r / min under nitrogen protection for 15 min, heated to 52.5°C, and added with an equal molar amount of diethyl maleate to 4',4" (5")-diaminodibenzo-15-crown ether-5 at a uniform rate over 9 min, heated to 80°C, stirred for 35 h, and dried at 55°C for 23 h to obtain a capping agent;
[0085] (5) Mix polyaspartic acid resin F420, polyaspartic acid resin F524, hexamethylene diisocyanate-based polyisocyanate trimer and tetrahydrofuran in a molar ratio of 1:1:1.9:9, stir at 60°C and 250 r / min for 60 min, cool to 50°C, continue stirring, uniformly add 3.5 times the molar amount of polyaspartic acid resin F420 in 9 min, cool to 40°C, continue stirring for 3 h, and obtain modified polyurea;
[0086] (6) The modified polyurea and the functionalized alumina were mixed in a mass ratio of 1:0.2, stirred at 40°C and 250 r / min for 5 min to obtain a coating material, sprayed on the glass surface, vacuum dried at 60°C for 72 h, and allowed to stand at room temperature for 72 h to obtain a temperature-resistant glass.
[0087] The length of the silicon whisker in step (1) is 3 μm.
[0088] The thickness of the plate in step (1) is 20 mm.
[0089] The ethanol solution in step (2) is prepared by uniformly mixing ethanol and water in a mass ratio of 1:1.
[0090] The specific operation of the drying in step (2) is vacuum drying at -5°C for 24 hours.
[0091] The mixed solution in step (5) is prepared by uniformly mixing the functionalized monomer, the end-capping agent and tetrahydrofuran in a molar ratio of 4:1:9.
[0092] The spraying thickness of the coating material in step (6) is 2 mm.
[0093] Comparative Example 2
[0094] A method for preparing a temperature-resistant glass material mainly comprises the following preparation steps:
[0095] (1) 25 parts of silicon whiskers, 45 parts of nano silicon dioxide, 3 parts of lithium oxide, 2.5 parts of sodium carbonate, and 4.5 parts of titanium dioxide are taken by weight, and the silicon whiskers are immersed in an aluminum hydroxide solution for 2.5 minutes, taken out, and nano silicon dioxide, lithium oxide, sodium carbonate, and titanium dioxide are added, and the solution is kept at 1650° C. for 3 hours to obtain glass liquid, and the glass liquid is poured onto a graphite heating plate to obtain a plate, which is then transferred to an annealing furnace at 550° C. for annealing for 120 minutes, and naturally cooled to room temperature to obtain glass;
[0096] (2) Alumina, ethanol solution and 3-aminopropyltrimethoxysilane were mixed in a mass ratio of 1:90:0.4, ultrasonicated for 30 minutes, stirred at 60°C and 250 r / min for 24 hours, filtered, washed with ethanol for 4 times, and dried to obtain pre-modified alumina; pre-modified alumina and acetonitrile were mixed in a mass ratio of 1:11, 4-bromo-2-hydroxybenzaldehyde in an equal molar amount of 3-aminopropyltrimethoxysilane was added, stirred at 250 r / min for 16 hours, filtered, washed with ethanol for 4 times, and dried to obtain modified alumina;
[0097] (3) 2,2'-bis(trifluoromethyl)diaminobiphenyl and methanol were mixed in a mass ratio of 1:6, stirred at 250 r / min under nitrogen protection for 15 min, heated to 52.5°C, and diethyl maleate in an amount twice the molar amount of 2,2'-bis(trifluoromethyl)diaminobiphenyl was uniformly added within 9 min, heated to 80°C, stirred for 35 h, and dried at 55°C for 23 h to obtain a functionalized monomer;
[0098] (4) 4',4" (5")-diaminodibenzo-15-crown ether-5 and methanol were mixed in a mass ratio of 1:6, stirred at 250 r / min under nitrogen protection for 15 min, heated to 52.5°C, and added with an equal molar amount of diethyl maleate to 4',4" (5")-diaminodibenzo-15-crown ether-5 at a uniform rate over 9 min, heated to 80°C, stirred for 35 h, and dried at 55°C for 23 h to obtain a capping agent;
[0099] (5) Mix polyaspartic acid resin F420, polyaspartic acid resin F524, hexamethylene diisocyanate-based polyisocyanate trimer and tetrahydrofuran in a molar ratio of 1:1:1.9:9, stir at 60°C and 250 r / min for 60 min, cool to 50°C, continue stirring, uniformly add 3.5 times the molar amount of polyaspartic acid resin F420 in 9 min, cool to 40°C, continue stirring for 3 h, and obtain modified polyurea;
[0100] (6) The modified polyurea and modified alumina were mixed in a mass ratio of 1:0.2, stirred at 40°C and 250 r / min for 5 min to obtain a coating material, sprayed on the glass surface, vacuum dried at 60°C for 72 h, and allowed to stand at room temperature for 72 h to obtain a temperature-resistant glass.
[0101] The length of the silicon whisker in step (1) is 3 μm.
[0102] The aluminum hydroxide solution in step (1) is prepared by uniformly mixing aluminum hydroxide and water in a mass ratio of 1:4.
[0103] The thickness of the plate in step (1) is 20 mm.
[0104] The ethanol solution in step (2) is prepared by uniformly mixing ethanol and water in a mass ratio of 1:1.
[0105] The specific operation of the drying in step (2) is vacuum drying at -5°C for 24 hours.
[0106] The mixed solution in step (5) is prepared by uniformly mixing the functionalized monomer, the end-capping agent and tetrahydrofuran in a molar ratio of 4:1:9.
[0107] The spraying thickness of the coating material in step (6) is 2 mm.
[0108] A method for preparing a temperature-resistant glass material mainly comprises the following preparation steps:
[0109] (1) 25 parts of silicon whiskers, 45 parts of nano silicon dioxide, 3 parts of lithium oxide, 2.5 parts of sodium carbonate, and 4.5 parts of titanium dioxide are taken by weight, and the silicon whiskers are immersed in an aluminum hydroxide solution for 2.5 minutes, taken out, and nano silicon dioxide, lithium oxide, sodium carbonate, and titanium dioxide are added, and the solution is kept at 1650° C. for 3 hours to obtain glass liquid, and the glass liquid is poured onto a graphite heating plate to obtain a plate, which is then transferred to an annealing furnace at 550° C. for annealing for 120 minutes, and naturally cooled to room temperature to obtain glass;
[0110] (2) Mix 2,2'-bis(trifluoromethyl)diaminobiphenyl and methanol in a mass ratio of 1:6.
[0111] 250r / min, under nitrogen protection, stir for 15min, heat to 52.5℃, add diethyl maleate at a rate of 2 times the molar amount of 2,2'-bis(trifluoromethyl)diaminobiphenyl at a uniform rate within 9min, heat to 80℃, continue stirring for 35h, dry at 55℃ for 23h to obtain a functionalized monomer;
[0112] (3) 4',4" (5")-diaminodibenzo-15-crown ether-5 and methanol were mixed in a mass ratio of 1:6, stirred at 250 r / min under nitrogen protection for 15 min, heated to 52.5°C, and added with an equal molar amount of diethyl maleate to 4',4" (5")-diaminodibenzo-15-crown ether-5 at a uniform rate over 9 min, heated to 80°C, stirred for 35 h, and dried at 55°C for 23 h to obtain a capping agent;
[0113] (4) Mix polyaspartic acid resin F420, polyaspartic acid resin F524, hexamethylene diisocyanate-based polyisocyanate trimer and tetrahydrofuran in a molar ratio of 1:1:1.9:9, stir at 60°C and 250 r / min for 60 min, cool to 50°C, continue stirring, uniformly add 3.5 times the molar amount of polyaspartic acid resin F420 in 9 min, cool to 40°C, continue stirring for 3 h, and obtain modified polyurea;
[0114] (5) The modified polyurea and alumina were mixed in a mass ratio of 1:0.2, stirred at 40°C and 250 r / min for 5 min to obtain a coating material, sprayed on the glass surface, vacuum dried at 60°C for 72 h, and allowed to stand at room temperature for 72 h to obtain a temperature-resistant glass.
[0115] The length of the silicon whisker in step (1) is 3 μm.
[0116] The aluminum hydroxide solution in step (1) is prepared by uniformly mixing aluminum hydroxide and water in a mass ratio of 1:4.
[0117] The thickness of the plate in step (1) is 20 mm.
[0118] The mixed solution in step (4) is prepared by uniformly mixing the functionalized monomer, the end-capping agent and tetrahydrofuran in a molar ratio of 4:1:9.
[0119] The spraying thickness of the coating material in step (5) is 2 mm.
[0120] Comparative Example 4:
[0121] A method for preparing a temperature-resistant glass material mainly comprises the following preparation steps:
[0122] (1) 25 parts of silicon whiskers, 45 parts of nano silicon dioxide, 3 parts of lithium oxide, 2.5 parts of sodium carbonate, and 4.5 parts of titanium dioxide are taken by weight, and the silicon whiskers are immersed in an aluminum hydroxide solution for 2.5 minutes, taken out, and nano silicon dioxide, lithium oxide, sodium carbonate, and titanium dioxide are added, and the solution is kept at 1650° C. for 3 hours to obtain glass liquid, and the glass liquid is poured onto a graphite heating plate to obtain a plate, which is then transferred to an annealing furnace at 550° C. for annealing for 120 minutes, and naturally cooled to room temperature to obtain glass;
[0123] (2) Mix 2,2'-bis(trifluoromethyl)diaminobiphenyl and methanol in a mass ratio of 1:6.
[0124] 250r / min, under nitrogen protection, stir for 15min, heat to 52.5℃, add diethyl maleate at a rate of 2 times the molar amount of 2,2'-bis(trifluoromethyl)diaminobiphenyl at a uniform rate within 9min, heat to 80℃, continue stirring for 35h, dry at 55℃ for 23h to obtain a functionalized monomer;
[0125] (3) 4',4" (5")-diaminodibenzo-15-crown ether-5 and methanol were mixed in a mass ratio of 1:6, stirred at 250 r / min under nitrogen protection for 15 min, heated to 52.5°C, and added with an equal molar amount of diethyl maleate to 4',4" (5")-diaminodibenzo-15-crown ether-5 at a uniform rate over 9 min, heated to 80°C, stirred for 35 h, and dried at 55°C for 23 h to obtain a capping agent;
[0126] (4) Mix polyaspartic acid resin F420, polyaspartic acid resin F524, hexamethylene diisocyanate-based polyisocyanate trimer and tetrahydrofuran in a molar ratio of 1:1:1.9:9, stir at 60°C and 250 r / min for 60 min, cool to 50°C, continue stirring, uniformly add 3.5 times the molar amount of polyaspartic acid resin F420 in 9 min, cool to 40°C, continue stirring for 3 h, and obtain modified polyurea;
[0127] (5) The modified polyurea was stirred at 40°C and 250 r / min for 5 min to obtain a coating material, which was sprayed on the glass surface, vacuum dried at 60°C for 72 h, and allowed to stand at room temperature for 72 h to obtain a temperature-resistant glass.
[0128] The length of the silicon whisker in step (1) is 3 μm.
[0129] The aluminum hydroxide solution in step (1) is prepared by uniformly mixing aluminum hydroxide and water in a mass ratio of 1:4.
[0130] The thickness of the plate in step (1) is 20 mm.
[0131] The mixed solution in step (4) is prepared by uniformly mixing the functionalized monomer, the end-capping agent and tetrahydrofuran in a molar ratio of 4:1:9.
[0132] The spraying thickness of the coating material in step (5) is 2 mm.
[0133] Comparative Example 5:
[0134] A method for preparing a temperature-resistant glass material mainly comprises the following preparation steps:
[0135] (1) 25 parts of silicon whiskers, 45 parts of nano silicon dioxide, 3 parts of lithium oxide, 2.5 parts of sodium carbonate, and 4.5 parts of titanium dioxide are taken by weight, and the silicon whiskers are immersed in an aluminum hydroxide solution for 2.5 minutes, taken out, and nano silicon dioxide, lithium oxide, sodium carbonate, and titanium dioxide are added, and the solution is kept at 1650° C. for 3 hours to obtain glass liquid, and the glass liquid is poured onto a graphite heating plate to obtain a plate, which is then transferred to an annealing furnace at 550° C. for annealing for 120 minutes, and naturally cooled to room temperature to obtain glass;
[0136] (2) Alumina, ethanol solution and 3-aminopropyltrimethoxysilane were mixed in a mass ratio of 1:90:0.4, ultrasonicated for 30 minutes, stirred at 60°C and 250 r / min for 24 hours, filtered, washed with ethanol for 4 times, and dried to obtain pre-modified alumina; pre-modified alumina and acetonitrile were mixed in a mass ratio of 1:11, 4-bromo-2-hydroxybenzaldehyde in an equal molar amount of 3-aminopropyltrimethoxysilane was added, stirred at 250 r / min for 16 hours, filtered, washed with ethanol for 4 times, and dried to obtain modified alumina; modified alumina, 4-aminopyridine and acetone were mixed in a mass ratio of 1:0.15:9, stirred at 55°C and 250 r / min for 12 hours, filtered, washed with acetone for 4 times, and dried to obtain functionalized alumina;
[0137] (3) 4',4" (5")-diaminodibenzo-15-crown ether-5 and methanol were mixed in a mass ratio of 1:6, stirred at 250 r / min under nitrogen protection for 15 min, heated to 52.5°C, and added with an equal molar amount of diethyl maleate to 4',4" (5")-diaminodibenzo-15-crown ether-5 at a uniform rate over 9 min, heated to 80°C, stirred for 35 h, and dried at 55°C for 23 h to obtain a capping agent;
[0138] (4) Mix polyaspartic acid resin F420, polyaspartic acid resin F524, hexamethylene diisocyanate-based polyisocyanate trimer and tetrahydrofuran in a molar ratio of 1:1:1.9:9, stir at 60°C and 250 r / min for 60 min, cool to 50°C, continue stirring, uniformly add 3.5 times the molar amount of polyaspartic acid resin F420 in 9 min, cool to 40°C, continue stirring for 3 h, and obtain modified polyurea;
[0139] (5) The modified polyurea and the functionalized alumina were mixed in a mass ratio of 1:0.2, stirred at 40°C and 250 r / min for 5 min to obtain a coating material, sprayed on the glass surface, vacuum dried at 60°C for 72 h, and allowed to stand at room temperature for 72 h to obtain a temperature-resistant glass.
[0140] The length of the silicon whisker in step (1) is 3 μm.
[0141] The aluminum hydroxide solution in step (1) is prepared by uniformly mixing aluminum hydroxide and water in a mass ratio of 1:4.
[0142] The thickness of the plate in step (1) is 20 mm.
[0143] The ethanol solution in step (2) is prepared by uniformly mixing ethanol and water in a mass ratio of 1:1.
[0144] The specific operation of the drying in step (2) is vacuum drying at -5°C for 24 hours.
[0145] The mixed solution in step (4) is prepared by uniformly mixing the capping agent and tetrahydrofuran in a molar ratio of 1:9.
[0146] The spraying thickness of the coating material in step (5) is 2 mm.
[0147] Comparative Example 6:
[0148] A method for preparing a temperature-resistant glass material mainly comprises the following preparation steps:
[0149] (1) 25 parts of silicon whiskers, 45 parts of nano silicon dioxide, 3 parts of lithium oxide, 2.5 parts of sodium carbonate, and 4.5 parts of titanium dioxide are taken by weight, and the silicon whiskers are immersed in an aluminum hydroxide solution for 2.5 minutes, taken out, and nano silicon dioxide, lithium oxide, sodium carbonate, and titanium dioxide are added, and the solution is kept at 1650° C. for 3 hours to obtain glass liquid, and the glass liquid is poured onto a graphite heating plate to obtain a plate, which is then transferred to an annealing furnace at 550° C. for annealing for 120 minutes, and naturally cooled to room temperature to obtain glass;
[0150] (2) Alumina, ethanol solution and 3-aminopropyltrimethoxysilane were mixed in a mass ratio of 1:90:0.4, ultrasonicated for 30 minutes, stirred at 60°C and 250 r / min for 24 hours, filtered, washed with ethanol for 4 times, and dried to obtain pre-modified alumina; pre-modified alumina and acetonitrile were mixed in a mass ratio of 1:11, 4-bromo-2-hydroxybenzaldehyde in an equal molar amount of 3-aminopropyltrimethoxysilane was added, stirred at 250 r / min for 16 hours, filtered, washed with ethanol for 4 times, and dried to obtain modified alumina; modified alumina, 4-aminopyridine and acetone were mixed in a mass ratio of 1:0.15:9, stirred at 55°C and 250 r / min for 12 hours, filtered, washed with acetone for 4 times, and dried to obtain functionalized alumina;
[0151] (3) 2,2'-bis(trifluoromethyl)diaminobiphenyl and methanol were mixed in a mass ratio of 1:6, stirred at 250 r / min under nitrogen protection for 15 min, heated to 52.5°C, and diethyl maleate in an amount twice the molar amount of 2,2'-bis(trifluoromethyl)diaminobiphenyl was uniformly added within 9 min, heated to 80°C, stirred for 35 h, and dried at 55°C for 23 h to obtain a functionalized monomer;
[0152] (4) Mix polyaspartic acid resin F420, polyaspartic acid resin F524, hexamethylene diisocyanate-based polyisocyanate trimer and tetrahydrofuran in a molar ratio of 1:1:1.9:9, stir at 60°C and 250 r / min for 60 min, cool to 50°C, continue stirring, uniformly add 3.5 times the molar amount of polyaspartic acid resin F420 in 9 min, cool to 40°C, continue stirring for 3 h, and obtain modified polyurea;
[0153] (5) The modified polyurea and the functionalized alumina were mixed in a mass ratio of 1:0.2, stirred at 40°C and 250 r / min for 5 min to obtain a coating material, sprayed on the glass surface, vacuum dried at 60°C for 72 h, and allowed to stand at room temperature for 72 h to obtain a temperature-resistant glass.
[0154] The length of the silicon whisker in step (1) is 3 μm.
[0155] The aluminum hydroxide solution in step (1) is prepared by uniformly mixing aluminum hydroxide and water in a mass ratio of 1:4.
[0156] The thickness of the plate in step (1) is 20 mm.
[0157] The ethanol solution in step (2) is prepared by uniformly mixing ethanol and water in a mass ratio of 1:1.
[0158] The specific operation of the drying in step (2) is vacuum drying at -5°C for 24 hours.
[0159] The mixed solution in step (4) is prepared by uniformly mixing the functionalized monomer and tetrahydrofuran in a molar ratio of 4:9.
[0160] The spraying thickness of the coating material in step (5) is 2 mm.
[0161] Comparative Example 7:
[0162] A method for preparing a temperature-resistant glass material mainly comprises the following preparation steps:
[0163] (1) 25 parts of silicon whiskers, 45 parts of nano silicon dioxide, 3 parts of lithium oxide, 2.5 parts of sodium carbonate, and 4.5 parts of titanium dioxide are taken by weight, and the silicon whiskers are immersed in an aluminum hydroxide solution for 2.5 minutes, taken out, and nano silicon dioxide, lithium oxide, sodium carbonate, and titanium dioxide are added, and the solution is kept at 1650° C. for 3 hours to obtain glass liquid, and the glass liquid is poured onto a graphite heating plate to obtain a plate, which is transferred to an annealing furnace at 550° C. for annealing for 120 minutes, and naturally cooled to room temperature to obtain temperature-resistant glass;
[0164] The length of the silicon whisker in step (1) is 3 μm.
[0165] The aluminum hydroxide solution in step (1) is prepared by uniformly mixing aluminum hydroxide and water in a mass ratio of 1:4.
[0166] The thickness of the plate in step (1) is 20 mm.
[0167] Test Example 1:
[0168] Coating self-repair and aging resistance test:
[0169] Self-repair test method: The coating materials prepared in each embodiment and comparative example are made into strips with a length of 10 mm, a width of 4 mm, and a thickness of 1 mm, and the tensile performance test is carried out. The tensile fracture strength is tested at 5 mm / min. A small cut of 2 mm in length and 0.4 mm in depth is made transversely on the same sample, and the sample is left to stand at room temperature for 24 hours. The tensile fracture strength is tested again, and the repair efficiency is calculated, wherein the repair efficiency = tensile fracture strength after self-repair / tensile fracture strength before self-repair * 100%;
[0170] Aging resistance test method: The coating materials prepared in each embodiment and comparative example were made into strips with a length of 10 mm, a width of 4 mm, and a thickness of 1 mm, and the tensile performance test was performed. The tensile breaking strength was tested at 5 mm / min. The same sample was irradiated under a fluorescent ultraviolet lamp UV-A340 for 15 days, and the tensile breaking strength was tested. The tensile breaking retention rate was calculated, wherein the tensile breaking retention rate = tensile breaking strength after aging / tensile breaking strength before aging * 100%. The results are shown in Table 1.
[0171] Table 1
[0172] Repair efficiency Tensile break retention rate Example 1 98.6% 98.5% Example 2 99.1% 98.9% Example 3 98.9% 98.8% Comparative Example 1 99.0% 98.7% Comparative Example 2 74.5% 98.4% Comparative Example 3 73.9% 96.2% Comparative Example 4 74.0% 95.9% Comparative Example 5 98.5% 98.3% Comparative Example 6 75.1% 98.6% Comparative Example 7 —— ——
[0173] From the comparison of the experimental data in Table 1, it can be found that the coating of the temperature-resistant glass material prepared in the present invention has good self-repairing and aging resistance capabilities.
[0174] From the comparison of the experimental data of Examples 1, 2, 3 and Comparative Example 2 in Table 1, it can be found that the repair efficiency of Examples 1, 2, 3 is greater than that of Comparative Example 2, which shows that the modified alumina reacts with 4-aminopyridine to form a ligand that achieves a host-guest effect with the crown ether on the polyurea, so that the coating has the ability to self-repair;
[0175] From the comparison of the experimental data of Examples 1, 2, 3 and Comparative Example 3, it can be found that the tensile fracture retention rates of Examples 1, 2, 3 are greater than those of Comparative Example 3, which indicates that the reaction of alumina with 3-aminopropyltrimethoxysilane makes its surface rich in amino groups, and then reacts with 4-bromo-2-hydroxybenzaldehyde to form a conjugated ring, thereby making the coating resistant to aging.
[0176] Test Example 2:
[0177] Shock test:
[0178] The glass made by each embodiment and comparative example was made into a sample with a thickness of 6 mm, a length of 220 mm, and a width of 220 mm by a water jet, and then sprayed with a coating, and left to stand at room temperature for 7 days. The SHPB device of Southwest University of Science and Technology was used. The steel impact rod used in the test was a cylinder with a diameter of 20 mm, a length of 400 mm, and a weight of 0.96 kg, and the model was 60SiMnA. A laser velocimeter was installed at the entrance of the SHPB chamber. The initial speed of the impact rod leaving the chamber during the test was tested. The strain gauge was longitudinally pasted at a position 60 mm from the center point of the diagonal line of the back bullet surface of the specimen. During the test, a dynamic acquisition instrument was used to collect real-time strain. The high-speed camera was used for shooting at a frame rate of 20,000. The acquisition frequency of the dynamic acquisition instrument was 1 MHz, the impact velocity was 18 m / s, and the maximum deformation value of the test center was tested. The results are shown in Table 2.
[0179] Table 2
[0180] Center maximum deformation value Example 1 18.568mm Example 2 18.235mm Example 3 18.442mm Comparative Example 1 18.662mm Comparative Example 2 18.535mm Comparative Example 3 18.279mm Comparative Example 4 18.331mm Comparative Example 5 18.574mm Comparative Example 6 18.392mm Comparative Example 7 24.065mm
[0181] From the comparison of the experimental data in Table 2, it can be found that the temperature-resistant glass material prepared by the present invention has good impact resistance.
[0182] From the comparison of the experimental data of Examples 1, 2, 3 and Comparative Example 7 in Table 2, it can be found that the central maximum deformation values of Examples 1, 2, 3 are smaller than that of Comparative Example 7, which shows that the polyurea coating often exhibits a high failure strain when subjected to an impact load, thereby absorbing or dissipating the huge energy generated by the impact load, thereby enhancing the impact resistance of the material.
[0183] Test Example 3:
[0184] Thermal conductivity test:
[0185] Laser thermal conductivity meter test: The specific heat capacity of the sample is calculated by differential scanning calorimeter, and the thermal diffusion coefficient of the coating material is tested by laser thermal conductivity meter (LFA467). The coating materials prepared in each embodiment and comparative example are made into samples with a length of 5 mm, a width of 5 mm, and a thickness of 2 mm. The sample surface is sprayed with graphite before testing, and the thermal conductivity is calculated, wherein the thermal conductivity = sample thermal diffusion coefficient * sample density * sample specific heat capacity, and the differential scanning calorimeter is tested. The results are shown in Table 3.
[0186] Table 3
[0187] Thermal conductivity Example 1 0.3869W / (m·K) Example 2 0.3899W / (m·K) Example 3 0.3842W / (m·K) Comparative Example 1 0.3829W / (m·K) Comparative Example 2 0.3874W / (m·K) Comparative Example 3 0.3860W / (m·K) Comparative Example 4 0.1487W / (m·K) Comparative Example 5 0.3837W / (m·K) Comparative Example 6 0.3885W / (m·K) Comparative Example 7 ——
[0188] From the comparison of the experimental data in Table 3, it can be found that the temperature-resistant glass material coating prepared by the present invention has good thermal conductivity.
[0189] From the comparison of the experimental data of Examples 1, 2, 3 and Comparative Example 4 in Table 3, it can be found that the thermal conductivity of Examples 1, 2, 3 is larger than that of Comparative Example 4, which shows that alumina, as an inorganic non-metallic filler, can enhance the thermal conductivity of the coating.
[0190] Test Example 4:
[0191] Temperature change resistance test:
[0192] The thermal expansion coefficient of the glass produced in each embodiment and comparative example was tested in the temperature range of 30-500° C. by using a thermal expansion coefficient measuring instrument. The results are shown in Table 4.
[0193] Table 4
[0194] Coefficient of thermal expansion Example 1 <![CDATA[0.3977×10 -6 K -1 ]]> Example 2 <![CDATA[0.3915×10 -6 K -1 ]]> Example 3 <![CDATA[0.3942×10 -6 K -1 ]]> Comparative Example 1 <![CDATA[0.5283×10 -6 K -1 ]]> Comparative Example 2 <![CDATA[0.3933×10 -6 K -1 ]]> Comparative Example 3 <![CDATA[0.3960×10 -6 K -1 ]]> Comparative Example 4 <![CDATA[0.3985×10 -6 K -1 ]]> Comparative Example 5 <![CDATA[0.3924×10 -6 K -1 ]]> Comparative Example 6 <![CDATA[0.3947×10 -6 K -1 ]]> Comparative Example 7 <![CDATA[0.3950×10 -6 K -1 ]]>
[0195] From the comparison of the experimental data in Table 4, it can be found that the temperature change resistant glass material prepared by the present invention has good temperature change resistance.
[0196] From the comparison of the experimental data of Examples 1, 2, 3 and Comparative Example 1 in Table 4, it can be found that the thermal expansion coefficients of Examples 1, 2, 3 are smaller than that of Comparative Example 1, which indicates that when aluminum hydroxide is loaded on the surface of the whisker silicon, the high temperature causes the aluminum hydroxide to be converted into aluminum oxide, and aluminum oxide can reduce the thermal expansion coefficient of the glass, thereby achieving the effect of temperature resistance.
[0197] Test Example 5:
[0198] Antifouling test:
[0199] Test method: The temperature-resistant glass prepared in each embodiment and comparative example was cut into samples with a length of 10 cm and a width of 5 cm, and subjected to a 10-min droplet continuous rolling test (glycerol 45%) and a slurry pouring test (slurry 45 wt%), and then the droplet contact angle and the slurry contact angle were tested. The results are shown in Table 5.
[0200] Table 5
[0201] Droplet contact angle Mud contact angle Example 1 159.4° 151.3° Example 2 159.8° 151.7° Example 3 158.9° 151.6° Comparative Example 1 159.3° 150.9° Comparative Example 2 159.1° 151.0° Comparative Example 3 159.6° 151.4° Comparative Example 4 159.6° 151.8° Comparative Example 5 83.8° 79.2° Comparative Example 6 159.2° 151.3° Comparative Example 7 159.5° 151.1°
[0202] From the comparison of the experimental data in Table 5, it can be found that the temperature-resistant glass material prepared by the present invention has good anti-fouling ability.
[0203] From the comparison of the experimental data of Examples 1, 2, 3 and Comparative Example 5 in Table 5, it can be found that the droplet contact angle and the mud contact angle of Examples 1, 2, 3 are larger than those of Comparative Example 5, which shows that the fluorine atom has extremely strong electronegativity, so that the bond energy of the carbon-fluorine bond is large and the surface tension is extremely low, so that the modified polyurea can form a dense protective film on the surface of the material, thereby preventing the penetration of water, oil and stains, and achieving an anti-fouling effect.
[0204] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A temperature-resistant glass material, characterized in that: The temperature-resistant glass material is prepared by mixing modified polyurea with functionalized alumina to prepare a coating material, spraying it on the glass surface, and drying it; The functionalized alumina is prepared by reacting alumina with 3-aminopropyltrimethoxysilane, 4-bromo-2-hydroxybenzaldehyde and 4-aminopyridine in sequence; The glass is prepared by immersing whisker silicon in aluminum hydroxide solution, heating with nano silicon dioxide, lithium oxide, sodium carbonate and titanium dioxide, mixing and annealing. The modified polyurea is prepared by reacting polyaspartic acid ester resin F420, polyaspartic acid ester resin F524, hexamethylene diisocyanate-based polyisocyanate trimer, functionalized monomer and end-capping agent; The functionalized monomer is prepared by reacting 2,2'-bis(trifluoromethyl)diaminobiphenyl and diethyl maleate; The end-capping agent is prepared by reacting 4',4" (5")-diaminodibenzo-15-crown ether-5 and diethyl maleate.
2. A method for preparing a temperature-resistant glass material, characterized in that: The preparation method of the temperature-resistant glass material mainly includes the following preparation steps: (1) 20 to 30 parts of silicon whiskers, 40 to 50 parts of nano silicon dioxide, 2 to 4 parts of lithium oxide, 2 to 3 parts of sodium carbonate, and 4 to 5 parts of titanium dioxide are taken by weight, and the silicon whiskers are immersed in an aluminum hydroxide solution for 2 to 3 minutes, taken out, and nano silicon dioxide, lithium oxide, sodium carbonate, and titanium dioxide are added, and the solution is kept at 1600 to 1700° C. for 2 to 4 hours to obtain glass liquid, and the glass liquid is poured onto a graphite heating plate to obtain a plate, and the plate is transferred to an annealing furnace at 500 to 600° C. for annealing for 100 to 140 minutes, and naturally cooled to room temperature to obtain glass; (2) Alumina, ethanol solution and 3-aminopropyltrimethoxysilane are mixed in a mass ratio of 1:80-100:0.3-0.5, ultrasonicated for 25-35 minutes, stirred at 50-70°C and 200-300 r / min for 22-26 hours, filtered, washed with ethanol for 3-5 times, and dried to obtain pre-modified alumina; pre-modified alumina and acetonitrile are mixed in a mass ratio of 1:10-12, 4-bromo-2-hydroxybenzaldehyde in an equal molar amount of 3-aminopropyltrimethoxysilane is added, stirred at 200-300 r / min for 14-18 hours, filtered, washed with ethanol for 3-5 times, and dried to obtain modified alumina; The modified alumina, 4-aminopyridine and acetone are mixed in a mass ratio of 1:0.1-0.2:8-10, stirred at 50-60°C and 200-300 r / min for 11-13 hours, filtered, washed with acetone for 3-5 times, and dried to obtain functionalized alumina; (3) 2,2'-bis(trifluoromethyl)diaminobiphenyl and methanol are mixed in a mass ratio of 1:5-7, stirred at 200-300 r / min under nitrogen protection for 10-20 min, heated to 50-55° C., and diethyl maleate in an amount twice the molar amount of 2,2'-bis(trifluoromethyl)diaminobiphenyl is added at a uniform rate within 8-10 min, heated to 75-85° C., stirred for 34-36 h, and dried at 50-60° C. for 22-24 h to obtain a functionalized monomer; (4) 4',4" (5")-diaminodibenzo-15-crown-5 and methanol are mixed in a mass ratio of 1:5-7, stirred at 200-300 r / min under nitrogen protection for 10-20 min, heated to 50-55° C., and an equal molar amount of diethyl maleate is added to 4',4" (5")-diaminodibenzo-15-crown-5 at a uniform rate within 8-10 min, heated to 75-85° C., stirred for 34-36 h, and dried at 50-60° C. for 22-24 h to obtain a capping agent; (5) Mix polyaspartic acid resin F420, polyaspartic acid resin F524, hexamethylene diisocyanate-based polyisocyanate trimer and tetrahydrofuran in a molar ratio of 1:1:1.8-2:8-10, stir at 50-70°C and 200-300 r / min for 50-70 min, cool to 40-60°C, continue stirring, uniformly add a mixed solution of 3-4 times the molar amount of polyaspartic acid resin F420 within 8-10 min, cool to 30-50°C, continue stirring for 2-4 h, and obtain a modified polyurea; (6) The modified polyurea and the functionalized alumina are mixed in a mass ratio of 1:0.15-0.25, stirred at 30-50°C and 200-300 r / min for 4-6 min to obtain a coating material, sprayed on the glass surface, vacuum dried at 50-70°C for 70-74 h, and allowed to stand at room temperature for 70-74 h to obtain a temperature-resistant glass.
3. The method for preparing a temperature-resistant glass material according to claim 2, characterized in that: The length of the whisker silicon in step (1) is 1 to 5 μm.
4. The method for preparing a temperature-resistant glass material according to claim 2, characterized in that: The aluminum hydroxide solution in step (1) is prepared by uniformly mixing aluminum hydroxide and water in a mass ratio of 1:3 to 5.
5. The method for preparing a temperature-resistant glass material according to claim 2, characterized in that: The thickness of the plate in step (1) is 18 to 22 mm.
6. The method for preparing a temperature-resistant glass material according to claim 2, characterized in that: The ethanol solution in step (2) is prepared by uniformly mixing ethanol and water in a mass ratio of 1:
1.
7. The method for preparing a temperature-resistant glass material according to claim 2, characterized in that: The specific operation of the drying in step (2) is vacuum drying at -10 to 0°C for 22 to 26 hours.
8. The method for preparing a temperature-resistant glass material according to claim 2, characterized in that: The mixed solution in step (5) is prepared by uniformly mixing the functionalized monomer, the end-capping agent and tetrahydrofuran in a molar ratio of 3-5:1:8-10.
9. The method for preparing a temperature-resistant glass material according to claim 2, characterized in that: The spraying thickness of the coating material in step (6) is 2 mm.
Citation Information
Patent Citations
Modified alumina composite material, copper-coated substrate and preparation method of copper-coated substrate
CN104371274A
Transparent environment-friendly glassware
CN109320083A
Preparation process of electromagnetic wire for wind power generation
CN118762886A
High-strength corrosion-resistant aluminum-silicon glass and preparation method thereof
CN118791235A
A composition for Road surface marking and construction method of road sign using thereof
KR101974029B1
Cited By
High-weather-resistance photovoltaic panel coating material and preparation method thereof
CN120365778A
Corrosion-resistant glass and preparation method thereof
CN120483544A